Valuation of Top Three FMCG Companies in India - Venkatachalam, Aiswarya; Nalini, G. S. (Indian Journal of Finance, 2022)
Valuation is a quantitative method of determining the fair value of an asset or a company. Discounted cash flow is a valuation technique used to estimate the value of a company based on its future cash flows. The comparable company valuation method is used to evaluate the value of a company using the metrics of other comparable companies of similar size from the same industry. This study employed these two valuation techniques to determine the intrinsic value of the top three fast-moving consumer goods – personal care segment companies, namely Hindustan Unilever Limited, Dabur India Limited, and Godrej Consumer Products Limited. The financial metrics were extracted from the selected companies’ annual reports for 5 years from 2015 – 2019, and the stock price data were gathered from the National Stock Exchange. The explicit forecast was done for 5 years, from 2020 – 2024. This study concluded that these value-creating stocks would undoubtedly be wealth-creating stocks for investors.